The Effect of Right-Left Smash Drill Training Patterns on Smash Direction Accuracy in Badminton Athletes Aged 10-12 Years - Mochammad Dhiva Satria Elwanda; Anggi Setia Lengkana; Encep Sudirjo (Universitas Negeri Semarang, 2026)
The precise direction of a smash is an essential ability in badminton that must be cultivated from a young age. Nonetheless, numerous athletes aged 10 to 12 continue to experience difficulties with precise smash direction. Consequently, right-left smash workouts are essential for enhancing this skill. This study seeks to ascertain the baseline accuracy of athletes' smash direction abilities prior to the implementation of training interventions, hence establishing the fundamental skill level of the athletes. This study employs a quantitative technique utilising a pre-experimental design, especially a one-group pretest-posttest framework, to examine the effect of right-left smash training on smash direction accuracy in PB Sampoerna badminton competitors aged 10 to 12 years. The training occurred at PB. Sampoerna event in the North Sumedang District, Sumedang Regency, includes 20 participants aged 10 to 12 years, who were selected as research participants through a saturated sampling method. The research procedure includes initial measurements (pretest), providing treatment in the form of right-left smash. The results of the normality test show that the significance value (p-value) of the pretest data is 0.055, while the significance value of the posttest data is 0.569. Both significance scores exceed 0.05 (p > 0.05), indicating that the pretest and posttest data are regularly distributed. The statistical analysis of the paired sample t-test yielded a significance value (Sig. 2-tailed) of 0.000. This value is less than the designated significance level (α = 0.05). This indicates that the right-left smash drill training pattern has a significant effect. Systematic and repetitive practice has demonstrated enhancements in motor coordination, shot consistency, and shuttlecock directional control, leading to increased accuracy in smashes for athletes. The right-left smash training pattern is a useful technique for enhancing smash skills, especially directional precision, in young athletes.